WASPAS and ROC Algorithms for Faculty Senate Member Recruitment System - Santoso, Adinda Afriliya; Putri, Raissa Amanda (Sistemasi: Jurnal Sistem Informasi, 2024)
The Faculty Student Senate is a student organization that holds a control function as well as a legislative body and the highest representative of students on campus. The Faculty Student Senate also recruits several new members in accordance with predetermined criteria, the number of students who register to become SEMAF members is very large. If decision making is done manually, it is feared that the selection team for new members does not select objectively or nepotism occurs in the selection process. The purpose of this research is to Apply the WASPAS and ROC Methods to facilitate the selection of new members using the WASPAS method and ROC Weighting and Design and build a Website-based Decision Support System. This research uses the RnD Research and Development method. Based on the research results, the highest value is 0.9850, namely A23 and the lowest value is 0.4641, namely A30. By creating a WEB-based system using the ROC and WASPAS methods can produce an optimum value. Then the value can be used to determine the ranking on the SEMAF new member recruitment system